New tools for land preparation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The 'rollivator' is an animal-drawn cultivator developed by CEEMAT (Centre d'études et d'experimentation du machinisme agricole tropical) which enables land to be prepared for sowing immediately after the first rains. The rollivator is suitable...